PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK EMINA COSMETICS PADA DAN+DAN VILLA DAGO PAMULANG - Damayanti, Febrina; -, Munarsih (Jurnal Ilmiah Publika, 2023)
The purpose of this study was to determine the effect of product quality and brand image on purchasing decisions of Emina Cosmetics products at and + and Villa Dago Pamulang. The method used is quantitative, associative / quantitative research is research that aims to determine the relationship between two or more variables. With this research, a theory will be built that can function to explain, predict and control a phenomenon. The sampling technique used was saturated sampling and the sample in this study was 68 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. Y = 6,463 + 0,447X1 + 0,113X2. The value of the correlation coefficient or the level of relationship between the independent variable and the dependent variable was obtained at 0.871, meaning that it has a very strong relationship. The value of the coefficient of determination or the contribution of its influence simultaneously is 75.9% while the remaining 24.1% is influenced by other factors. Hypothesis testing is obtained by the calculated F value > Ftable or (102,266 > 3,14). Thus H0 is rejected and H3 is accepted. This means that there is a simultaneous significant effect of product quality and brand image on purchasing decisions